2015
DOI: 10.1167/iovs.15-17434
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standard Versus Wide-Field Composite Images of the Corneal Subbasal Layer by In Vivo Confocal Microscopy

Abstract: PURPOSE. To evaluate whether the densities of corneal subbasal nerves and epithelial immune dendritiform cells (DCs) are comparable between a set of three representative standard images of in vivo confocal microscopy (IVCM) and the wide-field mapped composite IVCM images.METHODS. This prospective, cross-sectional, and masked study included 110 eyes of 58 patients seen in a neurology clinic who underwent laser-scanning IVCM (Heidelberg Retina Tomograph 3) of the central cornea. Densities of subbasal corneal ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
1
43
0
1
Order By: Relevance
“…Notable exceptions are a study in a cohort of subjects with newly diagnosed type 2 diabetes, where mosaic images representing a mean of three or four IVCM fields of view were used, 4 and a study in healthy subjects and multiple sclerosis patients with mosaics having a mean of 7.7 fields of view. 23 In recent studies of contact lens wear, mosaics consisting of six fields of view were used. 24,25 In a single earlier study, 4 depth correction for SBP variation in the axial plane was performed whereas in other studies it is not performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable exceptions are a study in a cohort of subjects with newly diagnosed type 2 diabetes, where mosaic images representing a mean of three or four IVCM fields of view were used, 4 and a study in healthy subjects and multiple sclerosis patients with mosaics having a mean of 7.7 fields of view. 23 In recent studies of contact lens wear, mosaics consisting of six fields of view were used. 24,25 In a single earlier study, 4 depth correction for SBP variation in the axial plane was performed whereas in other studies it is not performed.…”
Section: Resultsmentioning
confidence: 99%
“…The time elapsed after diagnosis of diabetes, however, was associated with the progressive degradation of the corneal SBP as measured by mCNFL. To our knowledge this is the first study using wide-area mosaics in a large clinical cohort, representing an area of the SBP 5 23 to 10 4 times the area analyzed in prior cohort studies. In subjects aged 69 years in the present study, mCNFL declined by 1.9 mm/mm 2 in the diabetes group relative to those without diabetes, while the decline was 2.4 mm/mm 2 in long-duration diabetes relative to subjects with NGT.…”
Section: Discussionmentioning
confidence: 99%
“…Fabrik GmbH, Germany) as active ingredient was applied to both eyes, followed by a drop of lubricant 2 mg/g carbomer-containing gel (Vidisic gel®; Bausch & Lomb, Heidelberg, Germany). The IVCM imaging using “composite” mode was then performed as previously described in detail 2022 . The maximum possible corneal scan area in composite mode (3.2 mm × 3.2 mm) was acquired wherever possible (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…92 Further, a recent study showed that the corneal subbasal nerve density is comparable between a set of three representative standard IVCM images and wide-field mapped composite IVCM images. 93 Images should be selected from the layer immediately at or posterior to the basal epithelial layer and anterior to the Bowman’s layer. The selected images should be the best focused and most complete images, with the whole image in the same layer, without motion, without folds, and with good contrast.…”
Section: Assessment Of the Subbasal Corneal Nerve Plexusmentioning
confidence: 99%